2017
DOI: 10.1111/cen.13288
|View full text |Cite|
|
Sign up to set email alerts
|

The effects of coenzyme Q10 supplementation on glucose metabolism and lipid profiles in women with polycystic ovary syndrome: a randomized, double‐blind, placebo‐controlled trial

Abstract: Overall, CoQ10 supplementation for 12 weeks among subjects with PCOS had beneficial effects on glucose metabolism, serum total- and LDL-cholesterol levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 34 publications
4
36
0
Order By: Relevance
“…However, in another study, we have previously shown beneficial effects of CoQ10 on insulin metabolism and some lipid profiles in patients with PCOS [11], to our knowledge, this trial is the first evaluating effects of CoQ10 on gene expression related to insulin, lipid and inflammation among women with PCOS. We demonstrated that CoQ10 intake for 12 weeks among subjects with PCOS had beneficial effects on few gene expression related to insulin, lipid and inflammation.…”
Section: Discussionmentioning
confidence: 83%
“…However, in another study, we have previously shown beneficial effects of CoQ10 on insulin metabolism and some lipid profiles in patients with PCOS [11], to our knowledge, this trial is the first evaluating effects of CoQ10 on gene expression related to insulin, lipid and inflammation among women with PCOS. We demonstrated that CoQ10 intake for 12 weeks among subjects with PCOS had beneficial effects on few gene expression related to insulin, lipid and inflammation.…”
Section: Discussionmentioning
confidence: 83%
“…It must be kept in mind that in the current study, we considered 20% attrition rate in each group; this was based on our previous experience working with this population . However, we agree that most prior studies in this field had attrition rates of over 20%, in most of our projects conducted, attrition rates were always lower than 20% . Therefore, we considered 20% attrition rate in each group.…”
Section: Discussionmentioning
confidence: 93%
“…,35 Therefore, we considered 20% attrition rate in each group. This should be taken into account in the interpretation of our findings.Overall, adherence to the low-calorie DASH diet for 12 weeks among patients with PCOS had beneficial effects on weight and BMI loss, serum AMH, markers of insulin metabolism, SHBG, FAI, plasma NO and MDA levels, but did not affect other metabolic profiles.…”
mentioning
confidence: 99%
“…Jamilian et al (2017) found that supplementation with 4000 IU/day of vitamin D for 12 weeks to PCOS women resulted in significant decreases in serum insulin, HOMA-IR when compared with 1000 IU/day of vitamin D and placebo [35] . After CoQ10 treatment for 12 weeks, Samimi et al (2017) found significant decrease in HOMA-IR (-0.3±0.6 vs. +0.2±0.6, P=0.001) [33], which was in agreement with the present study. Insulin sensitivity was measured using QUICKI test which was significantly increased after CoQ10 supplementation in the current study and agreed by Samimi et al (2017) (+0.006±0.009 vs. -0.006±0.01, P<0.001) [33] , and a minimum increase after vitamin D supplementation that was agreed by previous studies [27,36] .…”
Section: Percentage Of Change (%)supporting
confidence: 93%